Design of Control System of Rapid and Quantitative Loading System Based on S7-400FH PLC - ZHU Zhen; LI Wei; YAN Ya (Gong-kuang zidonghua, 2011)
In order to meet with requirements of rapid and quantitative loading system of sulfur for petrochemical industry, a control system of rapid and quantitative loading system based on S7-400FH failure-safe PLC was designed. The paper introduced hardware and software design and network configuration of the control system in details. The practical application showed that the control system achieves rapid and quantitative loading of sulfur in dust environment, which has functions of centralized control, precise blending and self-protection interlock.